2017
DOI: 10.1016/j.enbuild.2017.04.046
|View full text |Cite
|
Sign up to set email alerts
|

A novel vertical greenery module system for building envelopes: The results and outcomes of a multidisciplinary research project

Abstract: (AAM) is copyrighted and published by Elsevier. It is posted here by agreement between Elsevier and the University of Turin. Changes resulting from the publishing process-such as editing, corrections, structural formatting, and other quality control mechanisms-may not be reflected in this version of the text. The definitive version of the text was subsequently published in ENERGY AND BUILDINGS,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 38 publications
0
31
1
Order By: Relevance
“…The most recent study [76] analyzed a real living wall and two types of plants-the Hedera helix and Bergenia cassifolia, and proposed a new method for measuring the absorption properties of living walls in situ. Another paper [77] also analyzed a real living wall, and confirmed that the high values of the sound absorption coefficient were mainly due to the presence of the substrate. Table 5.…”
Section: Reduction Of Noisementioning
confidence: 74%
See 1 more Smart Citation
“…The most recent study [76] analyzed a real living wall and two types of plants-the Hedera helix and Bergenia cassifolia, and proposed a new method for measuring the absorption properties of living walls in situ. Another paper [77] also analyzed a real living wall, and confirmed that the high values of the sound absorption coefficient were mainly due to the presence of the substrate. Table 5.…”
Section: Reduction Of Noisementioning
confidence: 74%
“…On the contrary, living walls cost more as they require nutrients and different watering system materials, which makes their design more complex. Another paper [77] compared the price for a living wall with a geotextile felt system on the market (750 €/m 2 ) with the price of same system experimentally made of recycled materials (400 €/m 2 ). [77] NSP: Not specified precisely; *: Empirical study.…”
Section: Type Of Vgs Type Of Construction Results Sourcementioning
confidence: 99%
“…The VGS canopy also acts as a ventilation blind, in which warm air is dissipated from the top and replaced by cool air from the exterior [30]. VGSs can thus reduce unwanted heat flows from outdoors to indoors, and serve as surrogate green spaces in building environments [31][32][33][34]. The application of VGSs with commonly used plant species on building envelopes can reduce steady-state heat conduction.…”
Section: Steady-state Heat Conductionmentioning
confidence: 99%
“…The possibility of implementing residential greenery, enhancing the supply of ecosystem services and improving the wellbeing of the inhabitants are many. Among the elements that can be implemented, worthy of note are the green walls, which can help to increase the level of biodiversity and reduce the urban heat island effect [52,53]. This improves the aesthetic quality of the residential greenery, encouraging residents to stay longer in the area.…”
Section: Discussionmentioning
confidence: 99%